2016
DOI: 10.17352/sjggt.000008
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of DNA Extraction and PCR Conditions for Genetic Diversity Study in Artemisia Herba- Alba from Algeria

Abstract: Background: Artemisia herba alba is an aromatic species very rich in secondary metabolites that can be used in traditional medicine. The context and purpose of the study: This species suffers from the degradation of its natural habitat. The creation of collections containing diverse ecotypes is important for its preservation. This species contains essential oils which limit the extraction of DNA. The objective of this study is to optimize the DNA extraction and PCR conditions. The method will be used to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…In our autogamous species A. herba-alba Ass o, the morphological variability between populations reflects the diversity of environmental conditions, but it is possible that performing mutants appear better adapted to the environment and rapidly diffuse, thanks to a strong autogamy. So, the morphological polymorphism demonstrated within our study sites and thus confirmed during our genetic study on the same species from the same site (Maghni et al, 2016) could be explained mainly by spontaneous mutations affecting this species. This study also indicated a great morphological diversity in A. herba-alba, which could help the choice of the most effective ecotypes for the reintroduction of this species in the degraded steppe ecosystems of Algeria and thus of North Africa.…”
Section: Discussionsupporting
confidence: 85%
“…In our autogamous species A. herba-alba Ass o, the morphological variability between populations reflects the diversity of environmental conditions, but it is possible that performing mutants appear better adapted to the environment and rapidly diffuse, thanks to a strong autogamy. So, the morphological polymorphism demonstrated within our study sites and thus confirmed during our genetic study on the same species from the same site (Maghni et al, 2016) could be explained mainly by spontaneous mutations affecting this species. This study also indicated a great morphological diversity in A. herba-alba, which could help the choice of the most effective ecotypes for the reintroduction of this species in the degraded steppe ecosystems of Algeria and thus of North Africa.…”
Section: Discussionsupporting
confidence: 85%